IV Certamen Crono-Teatro (2017). Modalidad de estación. 2. En Bavia - Pygmalión (Pygmalion. Revista de teatro general y comparado, 2025)
IV Certamen Crono-Teatro (2017). Modalidad de estación. 2. En Bavia